Electrochemical aptamer sensor for detection of SARS-CoV-2 S1 protein in real pharyngeal swab samples - Yi Wang; Rui Bao; Xin Zhang; Chao Wang; Chunxia Song; Min Song; Hongjuan Jiang; Tan Wang; Xiangwei Wu; Zhaofeng Luo; Ying Lu (Electrochemistry Communications)
The global impact of the COVID-19 (Corona virus disease 2019) pandemic has been significant and the reliability of widely used diagnostic methods was often hindered by high false-negative rates as well as instrumentation limitations. In this context, electrochemical aptamer sensors can offer various advantages, including high sensitivity, low cost and the ability to perform detection directly on body fluids without the need for expensive equipments. In this study, a sensor was developed by hybridizing a SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2)-specific spike glycoprotein (S protein) aptamer with sulfhydryl- and ferrocene-labeled single-stranded DNA complementary to the aptamer. This design exhibited enhanced sensitivity compared with the labeled aptamer alone. Furthermore, the sensor's sensitivity, specificity and reproducibility were validated, and the results showed a linear relationship with the logarithm of the S1 protein concentration, which ranged from 10 fM to 100 nM (ΔIp = 0.11 log CS1 protein / fM - 0.021, R2 = 0.99), with a LOD (limit of detection) of 1 fM (S/N = 3). Furthermore, the sensor successfully detected the S1 protein in pharyngeal swab samples from SAR S-CoV-2 patients. This study provides a promising approach for addressing public health crises and proposes a novel solution for managing infectious diseases during pandemics